Saint Kitts and Nevis Education Management Information System - Porta, Emilio; Klein, Jennifer; Arcia, Gustavo; Nannyonjo, Harriet (World Bank, Washington, DC, 2017)
The Education Management Information System (EMIS) in St. Kitts and Nevis is part of the Education Planning Division of the Ministry of Education. It functions in collaboration with the Chief Education Officer and other education officers. Four key objectives of St. Kitts EMIS have been established: collect and analyze educational data; inform policymakers; provide feedback to stakeholders; and monitor and support schools. This report includes the following headings: facilities and equipment, EMIS staff, EMIS data, data collection, data processing, and publications.